Tufted carpet : textile fibers, dyes, finishes, and processes - Moody, Von (Plastics Design Library., 2004)
This book combines Von Moody's original work and research in the carpet industry with the well respected 1986 textile source book, Textile Fibers, Dyes, Finishes, and Processes: A Concise Guide, by Howard L. Needles to produce a unique practical guide on all aspects of the preparation, manufacture, and performance of carpet. It addresses the structure and properties of fiber, carpet construction, coatings, dyes, finishes, performance, and recycling, among other topics. This volume is an indispensable reference for all practitioners in the carpet industry.